Hubungan Mutu Pelayanan Terhadap Kepuasan Pasien Di Instalasi Rawat Inap Rumah Sakit Umum Daerah Labuang Baji - Nurul Fadilah Cahyani Putri; Nurfardiansyah Bur; Nurbaeti (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Patient satisfaction results from a patient's assessment based on feelings about specific aspects of health services, such as staff behavior, facility cleanliness, and wait times, provided in a hospital. It can be said that how a patient evaluates the level of service quality, covering tangible and intangible factors, contributes to their overall satisfaction. This study aims to investigate the relationship between specific dimensions of health service quality and patient satisfaction at Labuang Baji Regional General Hospital in Makassar City. The type of research used is a quantitative study of patient satisfaction using a cross-sectional study design method. The study population was 160 people. The sample was 114 respondents. Hypothesis testing was carried out using the chi-square test. The instrument used was a questionnaire. The results of the study obtained a p-value of 0.000, meaning there is a relationship between tangibles and patient satisfaction, a p-value of 0.025 means there is a relationship between reliability and patient satisfaction, a p-value of 0.010 means there is a relationship between responsiveness and patient satisfaction, a p-value of 0.000 means there is a relationship between assurance and patient satisfaction, a p-value of 0.000 means there is a relationship between empathy and patient satisfaction at Labuang Baji Hospital, Makassar City in 2023. The study concludes that the variables of tangible, reliability, responsiveness, assurance, and empathy are related to patient satisfaction at Labuang Baji Hospital, Makassar City, in 2023. This study suggests that the hospital should continuously improve services in order to achieve patient satisfaction, especially for inpatients.